2015
DOI: 10.1007/s10964-015-0386-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Living Closer to a University Increase Educational Attainment? A Longitudinal Study of Aspirations, University Entry, and Elite University Enrolment of Australian Youth

Abstract: Geography remains a critical factor that shapes the development of aspirations, attainment, and choice in young people. We focus on the role of geography on university entry and aspirations due to the increasing requirement in society for a higher education qualification for access to prestigious positions in society. Using a large representative longitudinal database (N = 11,999; 50 % male; 27 % provincial or rural; 2 % Indigenous) of Australia youth we explore the association between distance to a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 50 publications
(67 reference statements)
3
38
0
1
Order By: Relevance
“…This statistical effect remains significant, however decreases, when controlling for individual characteristics in model 1b. This finding corresponds with previous literature that showed that distance to study opportunities plays a role in taking up studies (Frenette 2006;Parker et al 2016;Spieß and Wrohlich 2010;Tinto 1973). By utilizing travel-time radii we can extend this finding by quantifying the spatial scale in which study opportunities play a role.…”
Section: Empirical Findingssupporting
confidence: 89%
See 1 more Smart Citation
“…This statistical effect remains significant, however decreases, when controlling for individual characteristics in model 1b. This finding corresponds with previous literature that showed that distance to study opportunities plays a role in taking up studies (Frenette 2006;Parker et al 2016;Spieß and Wrohlich 2010;Tinto 1973). By utilizing travel-time radii we can extend this finding by quantifying the spatial scale in which study opportunities play a role.…”
Section: Empirical Findingssupporting
confidence: 89%
“…Emotional costs arise with distance from peers and family. A large number of studies conclude that distance has a negative effect on enrollment chances (Frenette 2006;Parker et al 2016;Spieß and Wrohlich 2010;Tinto 1973). Moreover, distance affects the type of college or university attended (Gibbons and Vignoles 2012) and the field of study (Denzler and Wolter 2011).…”
Section: Educational Infrastructure and The Transition To Universitymentioning
confidence: 99%
“…Nevertheless, to check the robustness of their results, all models were re‐estimated using an alternative measure of SES, the international socio‐economic index of occupational status. In all cases, results were similar regardless of which measure was used (Parker et al ).…”
Section: Contentmentioning
confidence: 69%
“…Por otro lado, el haber estudiado en la capital del país se mostró como un factor que predispone el tener mayor calificación y por ende estar apto para adjudicar una plaza. Esto puede deberse a que el Perú es una país con notoria desigualdad social que no incluye en su formación académica los conocimientos de pueblos andinos y amazónicos (17,18) , lo cual se traduce en presencia de mayores oportunidades educativas en la ciudad capital; esto debido a: i) la alta concentración de universidades, con lo cual existe una mayor variedad de opciones y costos educativos (19) y ii) la considerable densidad de profesionales con estudios de posgrado que migran a la ciudad de Lima, la cual supera el 60% y refleja la distribución centralista e inequitativa del país (20) .…”
Section: Discussionunclassified